Separate and Unequal: The Law of Domestic and International Terrorism - Sinnar, Shirin (2019)
U.S. law differentiates between two categories of terrorism. “International terrorism” covers threats with a putative international nexus, even when they stem from U.S. citizens or residents acting only within the United States. “Domestic terrorism” applies to political violence thought to be purely domestic in its origin and intended impact. The law permits broader surveillance, wider criminal charges, and more punitive treatment for crimes labeled international terrorism. Law enforcement agencies frequently consider U.S. Muslims “international” threats even when they have scant foreign ties. As a result, they police and punish them more intensely than white nationalists and other “domestic” threats. This legal divide not only harms individuals and communities but also reinforces distorted public perceptions of terrorism that fuel anti-immigrant and discriminatory policies. This Article is the first to challenge the domestic–international divide in U.S. terrorism law. It maps the divergence in the investigation, prosecution, and punishment of terrorism. It then refutes the three leading rationales for the divide: (1) civil liberties; (2) federalism; and (3) the magnitude of the threats. It further argues that, once the law divides threats into the “domestic” and “international,” the latter category will predictably expand to cover U.S. individuals perceived as “foreign,” even if they are citizens with negligible relationships abroad. Policymakers should reject the legal divide as both incoherent and invidious. But rather than “ratchet up” the criminalization of domestic terrorism in the name of equality, they should make the law’s approach to “international” terrorism more accountable and just